2005
DOI: 10.1159/000086892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paternal age on the frequency of cytogenetic abnormalities in human spermatozoa

Abstract: Many surveys have been performed to find etiological relationships between pregnancy outcome and specific risk factors, such as exposure to chemicals and radiation or parental age. Advanced maternal age is a strong risk factor for trisomic pregnancies, albeit there are considerable variations among the different chromosomes. The definite incidence of the various structural and numerical chromosome aberrations in spontaneous abortions and liveborns is well known, as well as the rate of maternally and paternally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 240 publications
2
48
1
2
Order By: Relevance
“…It is thought that spermatogonial stem cell divisions occurring over the life-course result in higher mutational rates and cytogenetic abnormalities in the sperm of older men (43,44). Numerous neurological and psychiatric disorders have been related to genomic alterations (45).…”
Section: Potential Etiological Mechanismsmentioning
confidence: 99%
“…It is thought that spermatogonial stem cell divisions occurring over the life-course result in higher mutational rates and cytogenetic abnormalities in the sperm of older men (43,44). Numerous neurological and psychiatric disorders have been related to genomic alterations (45).…”
Section: Potential Etiological Mechanismsmentioning
confidence: 99%
“…Sex chromosomal aneuploidies reveal a higher paternal contribution (Hassold and Hunt, 2001) with variations from about 6% in 47, XXX to 50% in 47, XXY and 100% in 47, XYY cases (Buwe et al, 2005), but age effects in the paternally derived cases were not found in small groups of 47, XXY men (Sloter et al, 2004).We compared the parental age of 228 Klinefelter patients with that of 224 men with severe infertility but normal karyotype, and found no significant age relation, neither to the father nor to the mother (Lanfranco et al, 2004).…”
Section: Aneuploidiesmentioning
confidence: 99%
“…There is no consensus on the relationship between males' age and aneouploidy in spermatozoa. Buwe et al 37 used human fluorescence in situ hybridization (FISH) karyotyping, which allows simultaneous analysis of several chromosomes in a shorter time. In addition, analysis can be made using a very low number of sperm cells, including samples retrieved from the genital tract or directly from the testicular tissue.…”
Section: Sperm Chromosomal Anomaliesmentioning
confidence: 99%
“…Evidence was found for an age-related increase in XY sperm disomy with advanced donor age (36-60 years compared with 18-35 years). 32,37 In addition, there is a more pronounced age-related effect on XX/YY disomy rate, a two-to three-fold higher frequency being seen when sperm originate from men of over 50 years. Dakouane et al 41 have examined testicular biopsies from 36 older men (61-102 years old) and 10 younger men (29-40 years old) by histomorphometry and FISH (X, Y and 18 chromosomes).…”
Section: Sperm Chromosomal Anomaliesmentioning
confidence: 99%